AUDIT AND DESIGNING OF A SERVICE-PRODUCTION PROCESS AT A COMPLEX PUBLIC CATERING ENTERPRISE - KRYVORUCHKO, MYROSLAV; ANTONENKO, АRTEM; RATUSHENKO, ANTONINA; GORKUN, ARTEM (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article argues the prospects of studying the service-production process of a complex public catering enterprise, which is due to possibility of reducing the estimated cost of the project by optimizing production and trade areas of an enterprise. Conducted literary review revealed lack of scientific and technical information on the relevant issues. Attention was focused on the role of process engineers who consolidate the designing process by agreeing initial data received from a project customer with design (contracting) organizations. There is an algorithm given how to design a service-production model of a complex public catering enterprise based on initial data – types of structural subdivisions, their number and seating capacity of dining halls. For analysis, an enterprise consisting of a restaurant seating 90 people and a pizzeria seating 30 people was taken. A principal structural service-production process scheme of the entity has been developed with a focus on conceptual principles of its activity. In accordance with predicted methods and forms of service, a spatial scheme of a service component of the entity activity has been proposed, reflecting interaction of visitors with trade area staff. Based on seating capacity of dining halls, with taking inclusive requirements into consideration, completion of premises for visitors with furniture and equipment has been fulfilled. Also, calculation of number of staff within one-shift and two-shift works has been made to ensure an appropriate level of service at structural subdivisions of the complex enterprise. The described service-production model is advisory in nature and, after carrying out marketing research, can serve as a starting point for business planning of financial and economic activities of public catering enterprises with a similar production and trade structure.
Keywords: audit; complex public catering enterprise; designing; process engineer; service-production process; restaurant; pizzeria; production shops; premises for visitors; equipment